2009
DOI: 10.3141/2136-10
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Multivariate Poisson Lognormal Models for Crash Severity Modeling and Site Ranking

Abstract: Traditionally, highway safety analyses have used univariate Poisson or negative binomial distributions to model crash counts for different levels of crash severity. Because unobservables or omitted variables are shared across severity levels, however, crash counts are multivariate in nature. This research uses full Bayes multivariate Poisson lognormal models to estimate the expected crash frequency for different levels of crash severity and then compares those estimates to independent or univariate Poisson log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(50 citation statements)
references
References 19 publications
4
45
1
Order By: Relevance
“…The multivariate approach takes into account that crash data of different severities or types are correlated, while the univariate approach fails to do so. Empirical evidence showed that the multivariate method of modelling crash data improves a model's goodness of fit (Aguero-Valverde and Jovanis, 2009;El-Basyouny and Sayed, 2009a;Ma et al, 2008;Park and Lord, 2007;Tunaru, 2002). However, despite the conceptual understanding and empirical evidence supporting the superiority of the multivariate approach over the univariate, its application to before-after safety evaluations has not been very common.…”
Section: Introductionmentioning
confidence: 97%
“…The multivariate approach takes into account that crash data of different severities or types are correlated, while the univariate approach fails to do so. Empirical evidence showed that the multivariate method of modelling crash data improves a model's goodness of fit (Aguero-Valverde and Jovanis, 2009;El-Basyouny and Sayed, 2009a;Ma et al, 2008;Park and Lord, 2007;Tunaru, 2002). However, despite the conceptual understanding and empirical evidence supporting the superiority of the multivariate approach over the univariate, its application to before-after safety evaluations has not been very common.…”
Section: Introductionmentioning
confidence: 97%
“…A second common approach is to use a mixing structure, in which one or more (typically) normally distributed random terms are introduced in the parameterization of the expected value of the discrete distribution (so that the expected value is not only a function of exogenous variables, but also includes one or more additive random terms within the exponentiation). If the same error term enters in the means of multiple count variables, this generates correlation (see Chib and Winkelmann, 2001, Lee et al, 2006, Park and Lord, 2007, Aguero-Valverde and Jovanis, 2009, and El-Basyouny and Sayed, 2009 for examples of such an approach). A similar, but slightly different mixing approach, has been used recently by Chiou and Fu (2012), who developed a multinomial-generalized Poisson model for the joint analysis of crash frequency and injury severity.…”
Section: Modeling Count Data By Typementioning
confidence: 99%
“…Several multivariate models have been employed such as multivariate spatial models (Song, 2004;Song et al, 2006), multivariate Poisson (MVP) models (Ma and Kockelman, 2006), and multivariate Poisson-lognormal (MVPLN) models (Park and Lord, 2007;Ma et al, 2008;Aguero-Valverde and Jovanis, 2009;El-Basyouny and Sayed, 2009). Compared to the univariate modelling approach, the multivariate models (i.e.…”
Section: Introductionmentioning
confidence: 99%